Matched population comparison of visual outcomes and patient satisfaction between 3 modalities for the correction of low to moderate myopic astigmatism - Ganesh S (Dove Medical Press, 2017)
Sri Ganesh, Sheetal Brar, Archana Pawar Phacorefractive Department, Nethradhama Superspeciality Eye Hospital, Bengaluru, Karnataka, India Purpose: To compare toric implantable collamer lens (T-ICL), femto-LASIK, and ReLEx SMILE for the treatment of low to moderate myopic astigmatism in terms of long-term visual and refractive outcomes and predictability of astigmatic correction.Materials and methods: The study included 30 eyes from 30 patients between the age groups of 21 and 40 years, undergoing bilateral surgery with any of the three procedures – T-ICL, femto-LASIK, or ReLEx SMILE – for correction of myopic astigmatism within the range of −3 to −8 D spherical equivalent (SE), with a minimum astigmatism of −0.75 D. Patients were followed up at day 1, 1 month, 6 months, and 1 year.Results: At 1 year, the mean cylinder reduced to −0.21±0.28, −0.17±0.36, and −0.22±0.28 D in the T-ICL, femto-LASIK, and ReLEx SMILE group, respectively. The predictability of astigmatism correction was comparable, with no statistically significant difference between the 3 groups (P>0.05). A total of 97% of eyes in ReLEx SMILE achieved a uncorrected distance visual acuity of 20/20 or better, compared to T-ICL (93%) and FS-LASIK (90%). However, gain in lines of corrected distant visual acuity (CDVA) was maximum in T-ICL group (60%). Four eyes in the femto-LASIK group had loss of CDVA by one line. Three eyes required exchange due to high vault and rotation of the T-ICL, which did not affect the final outcome.Conclusion: All 3 modalities were effective for myopic astigmatism at the end of 1 year. Quality of vision and patient satisfaction with T-ICL and ReLEx SMILE were similar and better than FS-LASIK. However, slight chances of postoperative rotation and exchange exist with T-ICL, which warrant thorough preoperative planning. Keywords: toric implantable collamer lens, femtosecond LASIK, ReLEx SMILE, myopic astigmatism